Are early measured resting-state EEG parameters predictive for upper limb motor impairment six months poststroke?. Issue 1 (January 2021) - Saes, Mique; Meskers, Carel G.M.; Daffertshofer, Andreas; van Wegen, Erwin E.H.; Kwakkel, Gert; ,
Highlights: Resting-state EEG parameters obtained within three weeks post stroke can predict upper limb motor impairment after six months. Brain Symmetry Index over the theta band is a prognostic biomarker in addition to Fugl-Meyer upper limb score at baseline. Resting-state EEG contains unique information regarding motor impairment outcome beyond clinical baseline scores. Abstract: Objectives: Investigate whether resting-state EEG parameters recorded early poststroke can predict upper extremity motor impairment reflected by the Fugl-Meyer motor score (FM-UE) after six months, and whether they have prognostic value in addition to FM-UE at baseline. Methods: Quantitative EEG parameters delta/alpha ratio (DAR), brain symmetry index (BSI) and directional BSI (BSIdir) were derived from 62-channel resting-state EEG recordings in 39 adults within three weeks after a first-ever ischemic hemispheric stroke. FM-UE scores were acquired within three weeks (FM-UEbaseline ) and at 26 weeks poststroke (FM-UEw26 ). Linear regression analyses were performed using a forward selection procedure to predict FM-UEw26 . Results: BSI calculated over the theta band (BSItheta ) (β = −0.40; p  = 0.013) was the strongest EEG-based predictor regarding FM-UEw26 . BSItheta (β = −0.27; p  = 0.006) remained a significant predictor when added to a regression model including FM-UEbaseline, increasing explained variance from 61.5% to 68.1%. Conclusion: Higher BSItheta values, reflecting more power asymmetry over the hemispheres, predict more upper limb motor impairment six months after stroke. Moreover, BSItheta shows additive prognostic value regarding FM-UEw26 next to FM-UEbaseline scores, and thereby contains unique information regarding upper extremity motor recovery. Significance: To our knowledge, we are the first to show that resting-state EEG parameters can serve as prognostic biomarkers of stroke recovery, in addition to FM-UEbaseline scores.